Application of Activity-Based Costing In Electronic Manufacturing - Nurul Farahin, Zamrud; Mohd Yazid, Abu; Nik Nurharyantie, Nik Mohd Kamil; Filzah Lina, Mohd Safeiee; Oktaviandri, Muchamad (2019)
An accurate product costing is very crucial in the production environment. The traditional cost accounting (TCA) has been reported to have limitations such as inaccurate cost allocation. This study explores the benefits of Activity-based Costing (ABC) in electronics manufacturing. Furthermore, it is to appraise the strength of cost driver in ABC in order to propose a better costing structure. To overcome the limitations of TCA, we applied ABC method to the costing structure of an electronic and electrical company. This costing method is applied at inductor production line. The data collected include labor cost, maintenance cost, material cost and consumable cost. All costing data are based on 2018 information. The product unit calculated by ABC is MYR 0.72 that is lower than TCA which is MYR 1.07 which is by 32.71% difference. Thus, ABC determined the actual cost of the product to be compared to current costing method that is TCA. In conclusion, ABC provides more accurate costing information to the company than current method that is TCA.